The Role of Amino Acid Substitution in HepT Toward Menaquinone Isoprenoid Chain Length Definition and Lysocin E Sensitivity in Staphylococcus aureus - Panthee, Suresh; Paudel, Atmika; Hamamoto, Hiroshi; Uhlemann, Anne-Catrin; Sekimizu, Kazuhisa (Frontiers in Microbiology, 2020)
Objectives: Staphylococcus aureus Smith strain is a historical strain widely used for research purposes in animal infection models for testing the therapeutic activity of antimicrobial agents. We found that it displayed higher sensitivity towards lysocin E, a menaquinone (MK) targeting antibiotic, compared to other S. aureus strains. Therefore, we further explored the mechanism of this hypersensitivity. Methods: MK production was analyzed by high-performance liquid chromatography and mass spectrometric analysis. S. aureus Smith genome sequence was completed using a hybrid assembly approach, and the MK biosynthetic genes were compared with other S. aureus strains. The hepT gene was cloned and introduced into S. aureus RN4220 strain using phage mediated recombination, and lysocin E sensitivity was analyzed by the measurement of minimum inhibitory concentration and colony-forming units. Results: We found that Smith strain produced MKs with the length of the side chain ranging between 8 – 10, as opposed to other S. aureus strains that produce MKs 7 – 9. We revealed that Smith strain possessed the classical pathway for MK biosynthesis like the other S. aureus. HepT, a polyprenyl diphosphate synthase involved in chain elongation of isoprenoid, in Smith strain harbored a Q25P substitution. Introduction of hepT from Smith to RN4220 led to the production of MK-10 and an increased sensitivity towards lysocin E. Conclusions: We found that HepT was responsible for the definition of isoprenoid chain length of MKs and antibiotic sensitivity.